Regenerative Medicine Using Non-Fetal Sources of Stem Cells - Bhattacharya, Niranjan; Stubblefield, Phillip George; SpringerLink (Online service) (London : Springer London : Imprint: Springer, 2015)
This book represents a major contribution to the emerging science of regenerative medicine using non-fetal sources of stem cells. The Editors, Dr Niranjan Bhattacharya and Professor Phillip Stubblefield, have brought together some of the most pre-eminent scientists working on regenerative medicine to share information on currently ongoing work in this area alongside unpublished observations that will help to shape the contours of future therapies. Regenerative Medicine: Using Non-Fetal Sources of Stem Cells discusses the potential clinical and therapeutic applications using non-fetal stem cells as well as providing instruction on the collection, isolation and characterization of stem cells from various non-fetal sources, such as menstrual blood, adipose tissue, breast milk and uprooted decidual teeth. This book will be an invaluable resource for both active researchers and those entering the field. The Editors truly hope that the text will act as a stimulant to professionals and clinical scientists, who may be inspired to further the work of the pioneering scientists who have contributed to this volume.
Multipotent Mesenchymal Stromal Cell-Based Therapies: Regeneration Versus Repair -- The Role Of Microenvironment Stromal Cells In Regenerative Medicine -- Identity Of Human Endometrial Tissue: Potent Source Of Stem Cells -- Endometrial Regenerative Cells and Exosomes Thereof for Treatment of Radiation Exposure -- Endometrial stem cells as potential cures for human diseases -- Menstrual Blood Transplantation Therapy for Stroke and other Neurological Disorders -- Characteristics and therapeutic potential of menstrual blood-derived stem cells -- Use of Animal Fats in Traditional Chinese Medicine -- Adipose-derived stem cells for therapeutic applications -- Subcutaneous adipose tissue derived stem cells: advancement and applications in regenerative medicine -- Expanded adipose tissue-derived stem cells for articular cartilage injury treatment: a safety and efficacy evaluation -- Redundant human omentum fat: a leap towards regenerative medicine -- Human Adipose-derived Stem Cells (ASC):Their Efficacy in Clinical Applications -- Potentialities of adipose-derived mesenchymal stem cells collected from liposuction for use in cellular therapy -- Stem cells from dental tissue for regenerative dentistry and medicine -- Dental Stem Cells Risk and Responsibilities -- Stem Cells & Deciduous Teeth Responsibilities -- Breastmilk Stem Cells: Recent Advances and Future Prospects -- Existence of mesenchymal-like somatic stem cells in the porcine uterus -- Human menstrual blood-derived stem cell transplantation for acute hind limb ischemia treatment in mouse models -- Of Baul behaviour, Stem Cell Primitive application? -- Application of Umbilical Cord and Cord Blood as alternative modes for Liver Therapy -- Crushed finger and its repair after placing it inside abdominal fatty tunnel for 6 weeks: A preliminary experience -- Understanding  the science behind  regeneration for its implications in medicine for future -- Uterine synechia: A preliminary communication on an attempted treatment of the condition with intrauterine instillation of autologous bone marrow monoclear cells -- Freshly collected amniotic fluid  and amniotic membrane as dressing material for Leprosy patients with gangrene: A preliminary report on an experience with 6 cases -- Use of fetal skin and amniotic fluid dressing  for non-healing burn patients in pediatric age group: A study of 5 cases -- Concern for pharmacogenomics and autologous cell therapy: Can this be a direction towards medicine for the future? -- Chronic wound of the skin and amniotic membrane based treatment potential -- Ethics and Moral principles in the practice of medicine.
Keywords: Hematology; Regenerative medicine; Tissue engineering; Stem cells; Hematology; Regenerative Medicine/Tissue Engineering; Stem Cells